The Importance of Key Performance Indicators when Eliminating Bottlenecks, Using Modern Research Methods in Process Management - Joanna LISOK (Communications of International Proceedings, 2020)
Implementation of the organization's basic strategic assumptions for measurable goals is a complicated and often tedious process. Most often it takes place behind closed doors, among the top management, whose determination and involvement in the implementation of the assumed tasks within the assumed period of time allow to realize actions aimed at achieving the assumed goal. Such an action is very important, because the guarantee of success is the assumption that the whole organization is going in one direction. It is a great challenge to build a clear and unambiguous way of communicating goals and the degree of their realization. The KPIs (Key Performance Indicators) and Result Indicators (RI) are the main tools to help. Tools supporting the Lean process approach in addition to indicators are the SMED method and the Spaghetti Chart method. The concept of SMED methodology was developed between 1950 and 1960, when Shigeo Shingo, a Japanese industrial engineer, in consultation with the Japanese company, considered its problems of inability to eliminate bottlenecks when creating TOYOTA car bodies using presses. The "bottlenecks" in the Japanese company were caused by long machine changeover times, which significantly affected production efficiency. Because Shigeo Shingo, considered to be the world's leading expert in production practices, was looking for the optimal solution for the factors that had a significant impact and control over the production processes that took place at the TOYOTA factory. The only effective solution was to reduce the company's expenses by minimizing the number of production batches, which shortened the machine changeover time. SMED system turned out to be a comprehensive tool. SMED (Single Minute Exchange of Die) is a one-digit minute changeover method. The machine change-over time for production is very important and significantly affects the flexibility and profitability of the production process. If we shorten the set-up time, it will be possible to produce more products in a shorter time, which will have a significant impact on the production flow. The change-over time will also allow to increase the range of manufactured components, which increases the company's attractiveness on the subcontractor market. Spaghetti chart is one of the tools of lean manufacturing. It is used to eliminate or reduce significantly losses in the production process. These include losses caused by overproduction, corrections, over processing, overstock, transport, and losses caused by waiting and movement. These losses occur in every production process and should be systematically reduced and eliminated. The spaghetti diagram is a visualization of movements and flows in the production process. With this method we can analyze both product, document and employee flows. With this tool you can find out which way an employee goes on the job, how much time it takes, what operations he performs and at what time. It also shows the distances and waiting times. When creating a diagram, it is necessary to pay special attention to the actual process, as it occurs in everyday work, with all its errors, flaws, problems. When creating a diagram, we focus on the real process even if it differs from standards and procedures. The Lean Management concept is based on delivering value to the customer. The current trend is to personalize services and products for its customers, optimize costs and processes. Managing a company is a big challenge, so it is worth trying to improve it with methods that are easy to implement. By using practical Lean Management solutions, production or sales results can be significantly improved. In the article the author will analyze modern Lean methods in order to develop guidelines for Lean Management.
Keywords: Lean; SMED methodology; Kaizen; 5W.